Biomass-Derived Catalysts with Dual Functions for Electrochemical Water Splitting - Wangchuang Zhu; Xinghua Zhang; Qi Zhang; Lungang Chen; Xiuzheng Zhuang; Longlong Ma (Energies)
With the continuous consumption of fossil energy and the related environmental problems, clean energy, especially the hydrogen energy-derived water electrolysis, has attracted wide attention. However, as a result of the high energy consumption of water electrolysis and the limitations of single-function catalysts, there is an urgent need for cheap and simple-to-make bifunctional catalysts. In this work, based on the NiFe-LDH that is usually used for OER (Oxygen Evolution Reaction), doping of heteroatoms was carried out and a bifunctional catalyst could be then prepared using biomass as the carbon source. The preparation of catalyst precursors and in situ reduction were performed through the coupling process of hydrothermal and pyrolysis to enhance the electrolytic activity of the catalyst. Results showed that the overpotentials required to reach a current density of 10 mA·cm−2 for the HER and OER processes were 305.2 mV and 310.4 mV, respectively, which are superior to the commercial catalysts. In the subsequent characterization, the structural characteristics of the catalyst support and their structure–activity correlation with active metals were systematically investigated by TEM, XRD, and XPS analysis, providing mechanistic insights into the catalytic behavior. The basic catalytic mechanisms of HER and OER were also obtained: the HER process was due to the formation of a Ni3Fe alloy structure during catalyst preparation, which changed the electronic structure of the catalyst, while the OER process was induced by the formation of a NiOOH intermediate. The research results are expected to provide new ideas and data support for the preparation of bifunctional catalysts.